A Design of Safe Communication Protocol for Secure Service Provision in Vehicular Communication Environments - Jin, Byung-Wook; Cha, Si-Ho (International Journal of Engineering and Technology, 2019)
Vehicular communication technology is being developed as an intelligent transportation system, and studies are being actively carried out to enhance the safety of vehicle driving and provide services with high efficiency in communication. Vehicular communication technology is evolving rapidly in order to realize fully autonomous vehicles, with the development of information technology (IT) and active technological development in national, enterprise and research institutes. However, the convergence with IT has created a vulnerability to cyber-attacks that occur between the vehicle and the transportation infrastructure, and therefore, research on security technology is required. The study designed a protocol to provide efficient and secure services in the vehicular communication environments. The security of the attack techniques occurring in the existing vehicular communication environment was analyzed and it was confirmed there was efficiency of 49% in the verification process compared to the protocol used in the communication environment and 71% in the verification process.Â Â